A Survey on Robust Modulation Requirements for the Next Generation Personal Satellite Communications - Ssimbwa, Julius; Lim, Byungju; Lee, Ju-Hyung; Ko, Young-Chai (Frontiers in Communications and Networks, 2022)
The unrelenting technological advancement in the generation of wireless networks in recent years has awakened the motion concerning the inclusion of satellites (Sats) in personal communications. Leveraging their ability to provide wide cover- age, uniform services, wide bandwidth, and so forth, Sat systems will be expected to co-exist with the current state-of-the-art infrastructure of terrestrial networks (TN). Herein, we present a comparative study on the representative digital modulation techniques for use in personal satellite communications (SatComs). We discuss the advantages and limitations of different modulation techniques, such as phase shift keying (PSK), continuous phase modulation (CPM), amplitude phase shift keying (APSK), and quadrature amplitude modulation (QAM). We also perform evaluations based on spectral efficiency, power efficiency, modulation error ratio (MER), error vector magnitude (EVM), and peak- to-average power ratio (PAPR) in the presence of high power amplifier (HPA) nonlinearities and Doppler effects. Comparisons in the form of tables, illustrations, and curves are also presented as verification for our literature findings. We further recommend the potential modulation techniques and present open issues that would reinforce personal SatComs.